Analisis Daya Saing Karet Alam Indonesia Di Pasar Internasional - Syahrudin; Heru Wahyudi; Ukhti Ciptawaty (BULLET : Jurnal Multidisiplin Ilmu, 2022)
This research attempts to analyze the competitiveness of Indonesia's natural rubber exports in the international market from 2009-2021. The analytical methods used in this study are Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), and Export Competitiveness Index (ECI). This study uses time series data with the object of research on Indonesian natural rubber during 2009-2021. The results of this study indicate that Indonesian rubber has strong competitiveness in the international market. The comparative advantage of Indonesia's natural rubber exports has a high value in 9 main export destination countries. The level of Indonesia's competitive advantage has fluctuated values during the study period. The results obtained from this research are expected to be one of the references in making policy directions related to the competitiveness and productivity of Indonesia's natural rubber. Indonesia must improve and maintain the quality and productivity of Indonesia's natural rubber to remain competitive in the international market.